Operating systems internals and design principles - Stallings, William (Pearson Education Limited, 2018)
Now in its 9th Edition, Operating Systems: Internals and Design Principles provides a comprehensive, unified introduction to operating systems topics aimed at computer science, computer engineering, and electrical engineering majors. Author William Stallings emphasizes both design issues and fundamental principles in contemporary systems, while providing readers with a solid understanding of the key structures and mechanisms of operating systems. He discusses design trade-offs and the practical decisions affecting design, performance and security. The text illustrates and reinforces design concepts, tying them to real-world design choices with case studies in Linux, UNIX, Android, and Windows 10.